Engagement in a structured physical activity program and its effects upon health-related quality of life in elderly women: An observational study - Cammisuli, Davide Maria; Franzoni, Ferdinando; Fusi, Jonathan; Scarfò, Giorgia; Castelnuovo, Gianluca (Frontiers in Psychology, 2023)
Aging is a complex process associated with an impairment in functional capacity and low health-related quality of life (HRQoL) due to a high frequency of chronic diseases in the elderly population. Regular physical activity (PA) may limit some physiological effects of sedentary lifestyle and increase life expectancy. An observational was conducted to measure the HRQoL among older adults living in the community, by comparing a convenience sample of elderly females practicing a structured program of PA from 2 to 3 times per week in 60-min sessions (i.e., active females, AFs) to a sample of participants adopting lifestyle behaviors expending little energy (i.e., sedentary females, SFs). A validated questionnaire (the RAND 36-item) was used as outcome measure. All participants were assessed in terms of cognitive status (Montreal Cognitive Assessment, MoCA) to exclude mild cognitive impairment, divided attention/executive functioning (Trail Making Test, Stroop Test) and psychopathological dimensions of anxiety (Geriatric Anxiety Inventory, GAI), and depression (Geriatric Depression Scale, GDS). Non-parametric analysis revealed that AFs and SFs differed significantly in the RAND Energy/Fatigue (E/F), Emotional Wellbeing (EW), and Social Functioning (SoF), that was however influenced by education level. Moreover, E/F and EW were negatively associated to anxiety and depression, while SoF was influenced by divided attention. PA results in a healthful behavior for combating feelings of fatigue and low energy as well as emotional distress that can affect health status perception in older women.